2022
DOI: 10.1186/s12875-021-01617-3
|View full text |Cite
|
Sign up to set email alerts
|

Misbeliefs about non-specific low back pain and attitudes towards treatment by primary care providers in Spain: a qualitative study

Abstract: Aim To identify misbeliefs about the origin and meaning of non-specific chronic low back pain and to examine attitudes towards treatment by primary health care providers. Design Generic qualitative study. Methods Ten semi-structured interviews were conducted between October and November 2016 with physicians and nurses from primary health care centres in Lleida. The interviews were transcribed and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The findings of this study align closely with previous research conducted in various countries, including the UK, Canada, and New Zealand. In those studies, the mean scores for the biomedical and bio-psychosocial subscales were consistently reflected at 30.7 and 43.4, respectively, showcasing a level of consistency across different geographical contexts [9,[20][21][22]. However, other studies reported slightly different findings, with some studies reporting a higher score for the bio-psychosocial subscale and a lower score for the biomedical subscale.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The findings of this study align closely with previous research conducted in various countries, including the UK, Canada, and New Zealand. In those studies, the mean scores for the biomedical and bio-psychosocial subscales were consistently reflected at 30.7 and 43.4, respectively, showcasing a level of consistency across different geographical contexts [9,[20][21][22]. However, other studies reported slightly different findings, with some studies reporting a higher score for the bio-psychosocial subscale and a lower score for the biomedical subscale.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies reported that the treatment selection for CLBP is not solely influenced by physiotherapists' fear-avoidance beliefs but is instead influenced by various factors, such as their understanding of pain, education, and other individual and environmental factors [19,20]. Accordingly, this study discerns the beliefs and attitudes of Indian physiotherapists regarding the choice of treatments for low back pain and its correlation with the selected models of pain.…”
Section: Introductionmentioning
confidence: 91%
“…Instructed therapeutic exercise could be one of the first-line options for treatment of chronic musculoskeletal pain ( Babatunde et al, 2017 ). A previous qualitative study of primary care physicians and nurses and revealed that they believe therapeutic exercise can be beneficial in the treatment of chronic low back pain but do not necessarily prescribe it, rather tending to limit physical exercise and work activity in patients ( García-Martínez et al, 2022 ). This could be due to fear-avoidance beliefs of the medical professional themselves ( Darlow et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“… 32 Another example of practitioner-related misbeliefs about NSCLBP management can be illustrated by an investigation conducted with general practitioners in Spain. 33 The authors of this qualitative study identified that interviewed general practitioners considered therapeutic exercise as a suitable approach to NSCLBP management but hesitated to prescribe it and continued to educate patients about postural hygiene or recommended limiting activities contrary to recommendations of international practice guidelines. 33 …”
Section: Discussionmentioning
confidence: 99%